2022
DOI: 10.3390/nu14214549
|View full text |Cite
|
Sign up to set email alerts
|

L-Citrulline Supplementation Restrains Ferritinophagy-Mediated Ferroptosis to Alleviate Iron Overload-Induced Thymus Oxidative Damage and Immune Dysfunction

Abstract: L-citrulline (L-cit) is a key intermediate in the urea cycle and is known to possess antioxidant and anti-inflammation characteristics. However, the role of L-cit in ameliorating oxidative damage and immune dysfunction against iron overload in the thymus remains unclear. This study explored the underlying mechanism of the antioxidant and anti-inflammation qualities of L-cit on iron overload induced in the thymus. We reported that L-cit administration could robustly alleviate thymus histological damage and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 79 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…For example, Man et al have revealed that citrulline attenuates the progression of pre‐eclampsia by suppressing the NF‐κB pathway 33 . In addition, Ba et al have identified that citrulline inhibits ferroptosis in the thymus via inactivating the NF‐κB pathway 34 . Herein, we predicted that citrulline could combine with p65.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, Man et al have revealed that citrulline attenuates the progression of pre‐eclampsia by suppressing the NF‐κB pathway 33 . In addition, Ba et al have identified that citrulline inhibits ferroptosis in the thymus via inactivating the NF‐κB pathway 34 . Herein, we predicted that citrulline could combine with p65.…”
Section: Discussionmentioning
confidence: 84%
“… 33 In addition, Ba et al have identified that citrulline inhibits ferroptosis in the thymus via inactivating the NF‐κB pathway. 34 Herein, we predicted that citrulline could combine with p65. However, whether citrulline mediated the NF‐κB pathway to participate in pyroptosis in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal alteration in the mitochondrial membrane potential is not only an important marker of mitochondrial damage but also an early warning of ferroptosis . For more visual observation of cellular ferroptosis, we examined the morphology of the HOS cells by TEM.…”
Section: Resultsmentioning
confidence: 99%
“…The abnormal alteration in the mitochondrial membrane potential is not only an important marker of mitochondrial damage but also an early warning of ferroptosis. 46 For more visual observation of cellular ferroptosis, we examined the morphology of the HOS cells by TEM. The cells treated with FDPM or Fe 3 O 4 nanoparticles exhibited only evident swelling of mitochondria, which was consistent with previous reports.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…It has been demonstrated that the anti-inflammatory drug quercetin may inhibit ferroptosis, via the PI3K/AKT/mTOR pathway ( Lan et al, 2022 ). L-cit, which has anti-inflammatory properties, may target ferritin phagocytosis and mediate ferroptosis ( Ba et al, 2022 ). A review by Li et al described the active glycoside component of the medicinal plant Anoectochilus roxburghii , kinsenoside (KD), which also has potent anti-inflammatory and antioxidant properties.…”
mentioning
confidence: 99%